Decision Support System for Recruitment of General Election Committee using The Simple Additive Weighting - Khairani, Ica; Hutagalung, Jhonson Efendi; Dewi, Muthia (Jurnal Pendidikan Informatika (EDUMATIC), 2024)
In the voting process in general elections, committee errors often occur in carrying it out. So the results of the number of votes took a long time to obtain due to the dynamics that existed during the process and the occurrence of counting errors. The purpose of this research is to build a system by applying the SAW method in determining the voting committee selection committee.  The type of research used is Research and Development with the system development model using a prototype model with the stages of requirements gathering and analysis, quick design, building prototypes, user evaluation, implementing products and maintaining them, and requirements gathering and analysis. Then the data is analyzed using the Simple Additive Weighting (SAW) method by providing certain types of criteria that have weights so that the final value obtained through ranking becomes the final decision. The application was built using the PHP language and a MySQL database. The results of members who pass are then reported to the sub-district voting committee as a research object. The data was calculated from 10 people from each electoral district where they served. So from those 10 people, 7 people will be selected.